Daytime radiative cooling purposes with selective multilayer design based on Ta2O5 - Mabchour, G.; Benlattar, M.; Saadouni, K.; Mazroui, M. (Optik (Stuttgart), 2020)
Nighttime radiative cooling is the natural phenomenon by which the radiators lose heat via thermal radiation using the transparency window (8–13) μm. Historically, nighttime radiative cooling purposes have been investigated for a long time, but daytime radiative cooling has not been yet extensively studied. The daytime cooling operation requires a cover shield, which not only provides extremely high mid-infrared emissivity, but also rejects solar radiation. In this paper, we study numerically a multilayer structure that has both high emissivity in atmospheric window and high reflectivity in the visible and near infrared spectrums, which are difficult to achieve simultaneously. In this study, we propose alternative design for 2D thin film coatings, with periodic segments of Ta2O5 and SiO2. The selective optical properties of our design have been optimized in order to improve cooling performance. In this context the transfer matrix formalism was applied to determine the average optical properties. The multilayer conception can provide a high-performance cooling system exceeding 87 W/m2 at an ambient temperature of 300K under direct sunlight, giving to a temperature reduction of 20 °C. More than 95 % of the solar irradiation can be reflected, and the average emissivity in the sky window is larger than 85 %. We believe the proposed design is suitable for daytime radiative cooling purposes and temperature control applications.